Relationship between Personality Types and Job Satisfaction among Employees in Malaysian Manufacturing - Mohamed, Muhamed Shabir Bashir; Asaari, Muhammad Hasmi Abu Hassan; Desa, Nasina Mat (Universiti Sains Malaysia, 2016)
Employee job satisfaction is one of the important measurement aspects of an employee work life. Over the years, rich and mass knowledge in terms of academic research and management practice has been collected to understand further employee job satisfaction, especially for a firm, which work design is highly dependent on human workforce. Manufacturing industry is categorized under this group. Employee job satisfaction could be explained in terms of employee personality. As such, this research is design to understand the relationship between personality type and job satisfaction level of employees. For this paper, blue collar employees from manufacturing industry ware chosen. It is hoped that this paper could contribute to the body of knowledge on this field and further help manufacturing firms to explore options in increasing their workers’ job satisfaction level so that in the long term the firm can achieve its mission and vision.